Implementasi Program Bina Pribadi Islam (BPI) Dalam Menanamkan Nilai-Nilai Karakter Peserta Didik Di SMP Islam Terpadu Harapan Bunda Manado - Mohamad Syakur Rahman; Rivai Bolotio; Rukmina Gonibala; Sriwahyuni Puluhulawa (IAIN Manado, 2022)
The implementation of Islamic Personal Development program in instilling character values for students at Harapan Bunda Manado Islamic Junior High School. This research discusses about the implementation of BPI program in instilling character values for students at Harapan Bunda Manado Islamic Junior High School. In the meantime, this following research limited to the problem of instilling the values of religious character, honesty, and responsibility of students by BPI program.The results show that the implementation of the program is carried out every Friday during school hours for one to two hours of lessons by dividing into classes. Meanwhile, the inculcation of the values of religious, honesty, and responsibility is applied by conveying the materials about the character values at the weekly BPI program, as well as the habits that routinely carried out in shool such as morning dhikr, strengthening homeroom teachers, sunnah dhuha prayers, congregational dzuhur prayers, shaum sunnah, cleaning duty, and school assignments